(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
The use of waste cooking oil for biodiesel synthesis reduces the cost of raw materials. After studying the appropriate conditions for biodiesel production in terms of the ratio of waste oil to methanol, the effect of reaction temperature, and the effect of reaction time by conducting a transesterification reaction with 1.0 %w/v sodium hydroxide as a catalyst. It was found from the analysis that the best ratio for biodiesel production is 1:3 ratio of waste oil to methanol, the best reaction temperature is at 60oC, and the best stirring time for the reaction mixture is 40 minutes. A large amount of biodiesel was prepared by applying the best conditions required to obtain the highest yield of the biodiesel, which was equal to 87.19% w/w after a five times wet washing process by 30 mL of distilled water. It was also found that the acid equivalent of biodiesel was 2.53 mg KOH /g, and biodiesel density ranged from 0.80 to 0.843 g / mL. The study proved that the biodiesel production process using waste cooking oil is technically feasible and inexpensive.